"Being one of the boys": perspectives from female forest industry leaders on gender diversity and the future of Nordic forest-based bioeconomy. Issue 6 (18th August 2019) - Baublyte, G.; Korhonen, J.; D'Amato, D.; Toppinen, A.
ABSTRACT: Women working in the Nordic forest sector are underrepresented in top leadership positions, despite the female share increasing in higher education programs. Little research exists on this niche actor group in the forest sector context. To fill this gap, we assess perceptions of female leaders on the state of gender diversity in the Nordic forest industry, on the future of the forest sector in the bioeconomy, and on the potential contribution the Nordic forest industry can make to empower women, as promoted by the UN Sustainable Development Goals. An elite interviewing strategy was used to engage female leaders working at the top management level of seven Finnish and Swedish forest companies. According to our results, adapting to "being one of the boys" appears to persist as a norm for female leaders in this masculine industry field. Participants believed that their influence on the industry's sustainability agenda comes from being in a senior management position, and is not a gender-related aspect. We conclude that the ability of the Nordic forest industry to adapt to strategic renewal into the bioeconomy will require a more diverse company culture, which is not solely gender-based and is fostered at all organizational levels.